Investigation of Outbreak-Specific Nonsynonymous Mutations on Ebolavirus GP in the Context of Known Immune Reactivity. (15th November 2018) - Vaughan, Kerrie; Xu, Xiaojun; Peters, Bjoern; Sette, Alessandro
Abstract : The global response to the most recent EBOV outbreak has led to increased generation and availability of data, which can be globally analyzed to increase our understanding of immune responses to EBOV. We analyzed the published antibody epitope data to identify regions immunogenic for humans on the main GP antigenic target and determine sequence variance/nonsynonymous mutations between historical isolates and variants from the 2013-2016 outbreak. Approximately half of the GP sequence has been reported as targeted by antibody responses. Our results show an enrichment of nonsynonymous mutations (NSMs) within epitopic regions on GP (70%, p = 0.0133 ). Mapping NSMs to human epitope reactivity may be useful for future therapeutic and prophylaxis development as well as for our general understanding of immunity against EBOV.